Odpowiedzi

2010-04-07T18:24:23+02:00
6-0,25x=0,75x-6
-0,25x-0,75x=-6-6
-x=-12/*(-1)
x=12

-2(x-10)-x=2(x-15)
-2x + 20-x= 2x-30
-3x-2x=-30-20
-5x=-50/:(-5)
x=10

2(x+5)+4=2(x-3)+x
2x+10+4=2x-6+x
2x-3x=-6-14
-x=-20/*(-1)
x=20

-15-5(2x-8)=59-4(3x-2)
-15-10x+40=59-12x+8
-10x+12x=59+8-25
-2x=42/:(-2)
x=-21

4x-3{2(x-1)+5}=4x-3(x+9)-15
4x-(2x-2+5)= 4x-3x-27-15
4x-2x+2-5=-x-42
2x+x=-42+3
3x=-39/:3
x=-13
2010-04-07T18:25:35+02:00
6-0,25x=0,75x-6
-0,25x-0,75x=-6-6
-x=-6
x=6

-2(x-10)-x=2(x-15)
-2x-20-x=2x-30
-2x-x-2x=20+30
-5x=50
x=-10

2(x+5)+4=2(x-3)+x
2x+10+4=2x-6+x
2x-2x-x=-10-4-6
-x=-20
x=20

-15-5(2x-8)=59-4(3x-2)
-15-10x+40=59-12x+8
-10x+12x=15-40+59+8
2x=33
x=16,5

4x-3{2(x-1)+5}=4x-3(x+9)-15
4x-3(2x-2+5)=4x-3x-27-15
4x-6x+6-15=-x-42
4x-6x+x=-6+15-42
-x=-33
x=33